Answer:
The value of x is ( 6 + i 4.79 ) and ( 6 - i 4.79 )
Step-by-step explanation:
Given Equation as :
x² - 12 x + 59 = 0
The equation is in the form of quadratic equation a x² + b x + c = 0
So, The value of x can be find as
x = [tex]\frac{- b \pm \sqrt{b^{2}- 4\times a\times c}}{2\times a}[/tex]
So substitute the value from given equation
I.e x = [tex]\frac{- (-12) \pm \sqrt{(-12)^{2}- 4\times 1\times 59}}{2\times 1}[/tex]
or, x = [tex]\frac{12 \pm \sqrt{144- 236}}{2}[/tex]
Or, x = [tex]\frac{12 \pm \sqrt{-92}}{2}[/tex]
Or, x = [tex]\frac{12 \pm i\sqrt{92}}{2}[/tex]
∴ x = [tex]6\pm i4.79[/tex]
Hence The value of x is ( 6 + i 4.79 ) and ( 6 - i 4.79 ) Answer